The Extent of Restrictions on the Service of Active-Component Military Women - Miller, Laura L. (RAND Corporation, 2012)
The National Defense Authorization Act for Fiscal Year 2011 mandated a review of gender-based assignment restrictions. To support this effort, RAND researchers analyzed service data to describe and quantify the military occupations that are closed to women, as well as occupations that are open with some positions that are closed.